Decontamination of soil contaminated with petroleum grease. (15th December 2009) - Rathod, G.W.; Rao, K.S.; Gupta, K.K.; Srivastava, R.K.; Tiwari, R.P.; Kumar, Jitendra
Contamination modifies the engineering properties of soil, thereby restricting its further use either as a construction material or as a supporting medium. Due to the scarcity of land, it becomes imperative to reuse the land for infrastructure developmental activities. Out of numerous soil contaminants, automobile grease is one of the most prominent. Considering the cumulative impact of contamination by grease on soil properties, its remediation has become inevitable. An experimental programme was undertaken to reclaim the soils contaminated with grease in this study. The performance of surfactant to remove the petroleum grease from soil and its effect on restoring the geotechnical properties was quantitatively evaluated. Locally available soil (clay with medium plasticity) was contaminated with varying percentages of grease, i.e., 3%, 6% and 9% by dry weight of soil. Geotechnical properties of virgin (0% grease), contaminated and decontaminated soils were determined. Surfactant, namely liquid organic cleaner (LOC) was employed to decontaminate the soil.